2000
DOI: 10.1111/j.1540-8159.2000.tb06761.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Electrocardiographic Predictors of Recurrent Atrial Fibrillation

Abstract: Patients with frequent episodes of paroxysmal atrial fibrillation (AF) are prone to develop permanent AF and have an increased thromboembolic risk. We have previously shown that P wave dispersion (P dispersion), defined as the difference between the maximum and the minimum P wave duration, and maximum P wave duration (P maximum) can distinguish patients with paroxysmal lone AF. The ability of those ECG markers and of other clinical and ECG variables to detect patients at risk for recurrent AF was tested in 88 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
219
1
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(229 citation statements)
references
References 41 publications
4
219
1
5
Order By: Relevance
“…P-wave dispersion, which is the difference between maximum and minimum P-wave duration, has been recently defined as a new electrographic marker for the prediction of atrial fibrillation (AF) 4 and it is found to be associated with inhomogeneous and discontinuous propagation of sinus impulses. 4,5 Although, in the Framingham Heart Study 6 body mass index (BMI) was not defined as an independent risk factor for AF, according to a recent study by Wang et al 7 obesity has proved as an important, potential risk factor for AF. The association of obesity with subsequent development of AF persists even after accounting for the influence of concominant conditions such as hypertension (HT), diabetes mellitus (DM) and myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…P-wave dispersion, which is the difference between maximum and minimum P-wave duration, has been recently defined as a new electrographic marker for the prediction of atrial fibrillation (AF) 4 and it is found to be associated with inhomogeneous and discontinuous propagation of sinus impulses. 4,5 Although, in the Framingham Heart Study 6 body mass index (BMI) was not defined as an independent risk factor for AF, according to a recent study by Wang et al 7 obesity has proved as an important, potential risk factor for AF. The association of obesity with subsequent development of AF persists even after accounting for the influence of concominant conditions such as hypertension (HT), diabetes mellitus (DM) and myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…The P wave corresponds to the far field induced by a specific electrical phenomenon on the cardiac surface, namely atrial depolarization. Hence, knowledge about the morphology and occurrence of the P wave is essential for the investigation of the atrial electrophysiology [2][3][4]. The long-term observation, in particular, helps to characterize the underlying dynamics and is, therefore, necessary for the classification of atrial diseases.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing recognition of the prognostic implications of the spatial variations of P-wave duration in normal individuals and patients with a variety of cardiac disease states 1-3. P-wave dispersion is defined as the deference between the maximum and minimum P-wave duration measured in a 12-lead electrocardiogram 4.…”
Section: Discussionmentioning
confidence: 99%
“…P-wave dispersion has been described as a non-invasive indicator of risk of atrial fibrillation 1. If atrial fibrillation occurs, the loss of atrial systolic contribution to the left ventricular diastolic filling results in progressive diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%